PERANAN ARBITRASE (BASYARNAS) DALAM PENYELESAIAN SENGKETA BISNIS SYARI’AH - Eko Siswanto (Al-Amwal : Journal of Islamic Economic Law, 2018)
Basyarnas as the agency authorized to settle business disputes Shari'ah has a very important role, including: resolving disputes with the principle of prioritizing civil peace efforts; resolving disputes over business operations using Islamic law can be resolved with the use of Islamic law; resolve the possibility of civil disputes between banks Shari'ah with customers or users of their services in particular, and among Muslims who perform civil relationships that make Islamic shari’ah as essentially in general is a genuine need real; and provide a simply and speedy settlement of disputes in civil muamalah or arising in the field of trade, industry, services and others. Basyarnas dispute settlement through confidence and security will be guaranteed for the parties to the dispute; the expertise of the arbitrators; arbitration is confidential; wisdom and sensitivity arbitrator; arbitration decisions more easily implemented than justice; rapid and cost-effective completion. The various stages of settlements, namely: a request to conduct the arbitration; Determination Arbiter; examination; peace; evidence and witnesses or experts; the end of the examination; decision making; improvement of the decision; cancellation of the decision; registration decision; implementation of the decision; and arbitration costs.